Colonization of grapes berries and cider by potential producers of patulin - Dana Tančinová (Potravinarstvo, 2015)
The aim of this study was to detect potential producers of mycotoxin patulin from grapes (berries, surface sterilized berries - endogenous mycobiota and grape juice) of Slovak origin. We analyzed 47 samples of grapes, harvested in 2011, 2012 and 2013 from various wine-growing regions. For the isolation of species we used the method of direct plating berries and surface-sterilized berries (using 1% freshly pre-pared chlorine) berries on DRBC (Dichloran Rose Bengal Chloramphenicol agar). For the determination of fungal contamination of grape juice we used plate-dilution method and DRBC and DG18 (Dichloran 18% Glycerol agar) as media. The cultivation in all modes of inoculation was carried at 25 ±1 °C, for 5 to 7 days. After incubation Aspergillus and Pencillium isolates were inoculated on the identification media. The potential producers of patulin were isolated from 23 samples berries, 19 samples of surface-sterilized berries and 6 samples of grape juice. Overall, the representatives of producers of patulin were detected in 32 (68.1%) samples (75 isolates). In this work we focused on the detection of potential producers of patulin, Penicillium expansum (the most important producer of patulin in fruits), Penicillium griseofulvum and Aspergillus clavatus were isolated. Chosen isolates of potential patulin producers were tested for the ability to produce relevant mycotoxins in in vitro conditions using thin layer chromatography method. The ability to produce patulin in in vitro condition was detected in 82% of isolates of Penicillium expansum, 65% of Penicillium griseofuvum and 100% of Aspergillus clavatus. Some isolates of Penicillium expansum were able to produce citrinin and roquefortine C, Penicillium griseofulvum cyclopiazonic acid, griseofulvin and roquefortin C, also. <!--[endif] -->